METODE WINDOW SHOPPING DENGAN PENUGASAN POSTER UNTUK PENCEGAHAN PEREDARAN NARKOBA DAN PEMBENTUKAN KARAKTER SISWA - Sugatri, Martini (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
To decrease the number of drug abuse which is getting more uncontrolled in Yogyakarta, all parties need to participate to cope with this problem. Board of National Narcotics has attempted to stop the growing of drug abuse by doing various efforts but the efforts are still the passive ones. Therefore, teachers need a suitable strategy to help avoid drug abuse among students.This paper will reveal the method Window Shopping through the task of making a poster to avoid the spread of narcotics and to build characters among students in teaching and learning activity of sociology. This method is used because it can arouse the active participation of students in class with the lesson material of avoiding the spread of narcotics in school. The Poster is made by the students so that they will be active to search for various sources, and this activity will produce products of posters that will be attached to the school walls. This method can also build and grow character values (creative, collaborate, communication and critical thinking).This kind of character education is very important to do in society to improve the quality of our nation and country